Konsep Islam Rahmatan lil ‘Alamain: Studi Komparatif Pemikiran Fethullah Gullen dan Farid Esack Mengenai Konsep Islam Kosmopolitan - Shari, Mira Fitri (UIN Sunan Kalijaga Yogyakarta, 2022)
This article describes the thoughts of the two reformers in the Islamic world, namely Fethullah Gulen and Farid Esack regarding the concept of Cosmopolitan Islam. The formulation of the problem from this article is how the concept of Cosmopolitan Islam is offered by the two figures? With this research. In this study it was found that, Fethullah Gulen was an influential figure in his homeland, Turkey. His thoughts talk about the Sufistic education that he initiated. The Sufistic education aims to be able to produce superior generations (Gold Generation), these generations are expected to become human beings who are not only devoted to Allah but also become human beings who always serve the community (hizmet), and are good at science. General and religion and respect for fellow human beings regardless of one’s background. Meanwhile, Farid Esack emphasizes the explanations of the verses of the Qur’an, where he uses the hermeneutic method to explain a hadith which he considers to be in accordance with the reality that exists in South Africa. His interpretations aim to prevent Muslims in particular from becoming human beings who do not care about the circumstances of the people around them.